2016
DOI: 10.1080/02640414.2016.1260150
|View full text |Cite
|
Sign up to set email alerts
|

Associations between prolonged sedentary time and breaks in sedentary time with cardiometabolic risk in 10–14-year-old children: The HAPPY study

Abstract: This study examines the association between prolonged sedentary time and breaks in sedentary time with cardiometabolic risk in 10-14-year-old children. This cross-sectional design study analysed accelerometry-determined sedentary behaviour and physical activity collected over 7 days from 111 (66 girls) UK schoolchildren. Objective outcome measures included waist circumference, fasting lipids, fasting glucose, blood pressure, and cardiorespiratory fitness. Logistic regression was used for the main data analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 48 publications
(69 reference statements)
1
55
1
4
Order By: Relevance
“…Some observational studies have reported significant associations between prolonged sitting and adverse health outcomes in 10- to 14-year-old children [17]. Similar findings have been reported in specific subgroups such as boys [18], children with low physical activity levels [19] or children with a family history of obesity [20].…”
Section: Introductionsupporting
confidence: 57%
“…Some observational studies have reported significant associations between prolonged sitting and adverse health outcomes in 10- to 14-year-old children [17]. Similar findings have been reported in specific subgroups such as boys [18], children with low physical activity levels [19] or children with a family history of obesity [20].…”
Section: Introductionsupporting
confidence: 57%
“…The remaining six studies (21%) [ 14 , 56 60 ] presented both. Fourteen of the 29 included studies (48%) adjusted for either total MVPA [ 14 , 33 , 36 , 38 , 40 42 , 58 ], sedentary time [ 60 ], or both MVPA and sedentary time [ 34 , 37 , 45 , 48 , 59 ]. The remaining 15 studies examined activity patterns without adjustment for total volume of sedentary time and/or physical activity [ 35 , 39 , 43 , 44 , 46 , 47 , 49 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies that have examined the association between physical activity and blood pressure in children have had inconsistent findings, with some showing that more time spent being active [ 15 – 25 ], and less time spent in sedentary behaviours [ 16 , 17 , 25 , 26 ], are associated with lower blood pressure or reduced risk of hypertension, and others finding no association between physical activity and blood pressure [ 27 33 ]. Several of these studies have been limited by self-reported measures of physical activity and sedentary time, both of which are subject to recall bias [ 15 , 18 , 19 , 32 ].…”
Section: Introductionmentioning
confidence: 99%